Grundtvigs syn på forkyndelsen - Regin, Prenter (Grundtvig-studier, 1948)
Grundvig's Views on Preaching. By Regin Prenter. On the first pulpit in Grundtvig’s Church in Copenhagen is an inscription: “ Read out what is written, and bear witness to what thou hast lived”. Many think that this strikingly expresses Grundtvig’s views on preaching the word. Preaching is life-testimony; therein lies its value, but also its limitation, for it is a human word, and cannot be ranked with God’s own word in Baptism and Holy Communion. Such a view of preaching is clearly opposed to that of Luther, who describes the preacher’s word as God’s own word, and refers to it as the “ living word” in contrast to the dead written word. No doubt this conception, which is inconsistent with the older Lutheran conception, is held by many of Grundtvig’s disciples, but did Grundtvig himself really hold it? In “ Den Christelige Bornelardom” Grundtvig writes of preaching as hope’s sign of life (“ Livstegn” ), just as the Creed is faith’s and the singing of hymns is love’s sign of life. We can see from the context here that preaching is regarded, not as the expression of an individual's experience, but as something which springs out of the Church's hope, just as the Creed expresses the Church's faith and hymns express the Church's love. To understand Grundtvig’s views on preaching we must consider them in connection with his whole conception of the nature of the Christian life, and in particular with his conception of faith, hope and love as the expression of the growing life of Christ in the Church and with his ideas about Church and school. Both in his hymns and in “ Den Christelige Bornelardom” we find many references to Grundtvig’s conception of Christian life as the presence and growth of Christ in the individual and the Church, beginning in blind-born faith, hastening onward through hope, and perfected in love. E. g. in “ Bornelardom” he speaks of the eternal word of life from the Lord’s own mouth as being threefold, like the Christian life: the word of faith, the word of hope, and the word of love (expressed in Baptism, the Lord’s Prayer, and Holy Communion). Only as this threefold word reaches its full power through faith and the spirit does the Church live its own life no longer, but Christ’s. Grundtvig criticises Lutheranism for regarding faith as the end, rather than the feeble beginning of the Christian life, and thus not giving their due place to hope and love. Nowadays, however, we seem to concentrate on what Grundtvig says of faith’s “ sign of life” , in Baptism, and neglect what he said of the Lord’s Prayer as hope’s “ sign of life” ; and the words of the Communion Service as love’s “ sign of life” and thus we have largely lost the strong sacramental realism of his conception of the Christian life as Christ’s own life in us, and tend to regard it as merely our own inner religious life. In emphasizing the nature of Christian life as a growth from faith through hope to love, Grundtvig, in spite of differences, has this in common with the other great nineteenthcentury Danish religious thinker, Kierkegaard, who insisted that “ Christian” is not something which one is, but something which one becomes. Grundtvig’s conception of the Christian life determines his views on the scriptures, theology and preaching, and his well-known distinction between Church and Christian school (“ Kirkeskole” , i.e . theology). Since Christ, without being what men call “ learned” , nevertheless knew and need the Jewish Scriptures, and after His Ascension chose the scholar Paul as one of His Apostles, it is clear that the Scriptures are indispensable, and Christian teachers, aided by the holy infallible Scriptures, are needed for the upbuilding of the Body of Christ (cf. Ephesians, IV, 11-13). In his “ Kirkelige Oplysninger” , Grundtvig stresses that the Scriptures are needed, not for the salvation of the individual, but for the enlightenment of the Church. Enlightenment (“ Oplysning”) is one of the most significant words in Grundtvig’s Christian philosophy. “ Oplysning” is the clear understanding of life that follows life’s growth; the Bible is a book that casts light on life, but does not, like Baptism, regenerate it. Enlightenment results in learning, but the “ living word” results in life. Here is the root of the distinction between Church and Christian school. The Church is the fellowship of those who live the life of faith; the school is the fellowship of those who, book in hand, seek enlightenment about life. But, referring to Ephesians, IV, 11-13, Grundtvig points out that as Christ’s Body comes nearer to the full measure of Christ, faith and understanding, Church and school, will come closer and closer together. Grundtvig considers it immensely important that the Church should stand firm as a rock in its faith, while the school should constantly move forward in its enlightenment. This view finds expression in an important passage in his “ Udvalgte Skrifter” (Selected Writings), IV, 663 ff. The impulse which makes the school move forward, while faith stands fast, is the same as that which leads the Christian life forward through hope to the perfection of love. There is therefore a special connection between the Christian school and hope. As Grundtvig put it in one of his hymns: “ The Church, built on faith, must remain secure on its foundation, while Hope goes to school” . As hope leads the Christian life nearer to its perfection, enlightenment also grows; and, seen from this standpoint, preaching is the means by which Christian teachers, the “ Christian school” , communicate this growing enlightenment to the whole Church. It is the word of Baptism, not preaching, that creates life; but the word of preaching springs from life, from life as hope, and prophesies what the Church shall be when it shall have grown up into Christ. Preaching in the Church thus corresponds in a way to mythology, which, in a nation’s youth, prophesies in poetic form what that nation’s life will be when it reaches its full unfolding. Luther regarded the preacher’s word as creating life; for Grundtvig it is the words of the sacraments that create life, and the preacher’s word only gives light; but this does not mean that it is not essential to the life of the Church, and a wondrous work of God. In “ Bornelardom” Grundtvig writes of the mysteries of the Christian life: “ the mystery of calling in the preaching of the gospel, the mystery of regeneration in Baptism, and the mystery of nurturing in Holy Communion” . The function of preaching in the life of the Church is to call us to Baptism and Holy Communion, through which alone the life of faith can be transmitted. But preaching is essential to the Church, and Grundtvig stresses its importance in what he writes about the miracle of Pentecost, e. g., in “ Udvalgte Skrifter” , X, 103f., and “ Sangvark” , II, 92 and 93. When we see Grundtvig’s conception of preaching as an integral part of his theory of the life of Christ and of the Church, it can hardly be claimed that he sets less value on the preacher’s word than Luther does. The singing of Grundtvig’s hymns about the Holy Spirit would be quite in tune with a Lutheran sermon. But Grundtvig’s conception of the nature of preaching is something much greater than can be expressed in the words: “ Read out what is written and bear witness to what thou hast lived” .